The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/frobt.2020.561774
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Wearable Robots: Challenges and Recommendations From Functional, User Experience, and Methodological Perspectives

Abstract: Wearable robots (WRs) are increasingly moving out of the labs toward real-world applications. In order for WRs to be effectively and widely adopted by end-users, a common benchmarking framework needs to be established. In this article, we outline the perspectives that in our opinion are the main determinants of this endeavor, and exemplify the complex landscape into three areas. The first perspective is related to quantifying the technical performance of the device and the physical impact of the device on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 52 publications
2
56
0
Order By: Relevance
“…Nevertheless, our survey data allowed a novel understanding and comprehensive review of WRD applications, their development stages and current usability evaluation practices. We could further elucidate the need for evaluation benchmarks and development guidelines, as it has been detailed and called for in recent works [19,25]. Our analysis may even support the benchmarking endeavors of initiatives such as the EUROBENCH project [41], the Exo Technology Center of Excellence from ASTM International [42] or the CY-BATHLON [43].…”
Section: Limitations and Implicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, our survey data allowed a novel understanding and comprehensive review of WRD applications, their development stages and current usability evaluation practices. We could further elucidate the need for evaluation benchmarks and development guidelines, as it has been detailed and called for in recent works [19,25]. Our analysis may even support the benchmarking endeavors of initiatives such as the EUROBENCH project [41], the Exo Technology Center of Excellence from ASTM International [42] or the CY-BATHLON [43].…”
Section: Limitations and Implicationsmentioning
confidence: 93%
“…More specifically, the application of relevant and appropriate usability evaluation measures remains a fundamental challenge in wearable robotics development [19].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such brain measurements provide only limited information (e.g., left vs. right arm movement), and their utility as a stand-alone method is thus questionable except for severely paralyzed individuals (AL-Quraishi et al, 2018); however, they could potentially be combined with more popular modalities such as EMG (Li et al, 2019). As another example, heart rate, respiration and other physiological measures are commonly used as a metric of wearer workload (physical or mental) and thus robot performance (Torricelli et al, 2020), and could be used to adapt the amount of robot assistance; however, while studies have suggested complex approaches to doing this (Schürmann et al, 2019), only limited work in this area has been done, mostly with stationary wearable robots (e.g., the Lokomat) (Koenig et al, 2011a,b).…”
Section: Sensingmentioning
confidence: 99%
“…However, they have limitations in both their technology (e.g., sensor quality, resolution, processing power) and assessment approach (e.g., simple tracking of body motion and pressure distribution as proxies for the evaluation of balance control). Research efforts are being made to develop more accurate portable and wearable technologies for quantitative balance assessment ( Conforti et al, 2020 ; Torricelli et al, 2020 ) by including, for instance, inertial measurement units or electromyographic devices ( Zampogna et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%